Measurement of Microfibril Angle Using X-Ray Diffraction and Light Microscope on 5-year-old Super and Conventional Teak Wood - Setiowati Setiowati; Ratih Damayanti; I. Ketut N. Pandit; Fauzi Febrianto; Gustan Pari (Masyarakat Peneliti Kayu Indonesia, 2014)
The long harvest time causes the processing industry manufactured from teak wood (Tectona grandis L. f.) has experienced a lot of declines. To overcome this problem, currently, in Indonesia many types of fast-growing teak have been developed, one of which is Jati Unggul Nusantara (JUN). Trees that are accelerated in growth, are likely to cause changes in their anatomical structure. The anatomical structure of wood is one of the basic properties that greatly influences the use of wood as a raw material. Even small changes in cell shape and size can change the properties of wood as a raw material. One of the anatomical structures of wood, namely the ultramicroscopic structure that affects the quality of wood, is the microfibril angle (MFA). The purpose of this study is to determine the MFA of JUN at the planned cutting age of 5 years, compared to conventional teak at the same age. There are two methods used, namely using X-Ray Diffraction (XRD) and measuring the elongation of the pit apertures slope of the fiber cells using a light microscope, which was obtained from the maceration process. As a result, JUN's MFA is 22.09°, smaller than the conventional teak of 25.29°. This is because JUN was developed from top cuttings so although still young, it already reflects the characteristics of mature teak. The results of the MFA measurements on JUN using two methods (XRD and light microscope), resulted different values. It is different from the MFA measurement results on conventional teak. It is recommended to measure the MFA in JUN wood by using XRD, because possibly, due to accelerated growth, simple pits with an oval shape turn into circular. This difference causes the results of the JUN MFA measurement using a light microscope based on the pit apertures slope to be inconsistent, subjective, and different results in other pits contained in the fiber even though they are closely associated. However, in conventional teak, measurements using a light microscope are possible because the shape of the pit is oval so that the slope of the elongation of the pit aperture can be determined easily, and is more consistent with more uniform values in the same individual fiber